2017
DOI: 10.1371/journal.pone.0172956
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent but not adult ethanol binge drinking modulates cocaine withdrawal symptoms in mice

Abstract: BackgroundEthanol (EtOH) binge drinking is an increasingly common behavior among teenagers that induces long-lasting neurobehavioral alterations in adulthood. An early history of EtOH abuse during adolescence is highly correlated with cocaine addiction in adulthood. Abstinence of cocaine abuse can cause psychiatric symptoms, such as anxiety, psychosis, depression, and cognitive impairments. This study assessed the consequences of adolescent exposure to EtOH on the behavioral alterations promoted by cocaine wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 69 publications
11
19
0
Order By: Relevance
“…7,8 Other studies demonstrate that chronic EtOH is more harmful, inducing greater long-term cognitive impairments when administered in adolescent animals than when this treatment is given in the adulthood. [9][10][11] Therefore, all this research confirms that both the way and the age of EtOH consumption is especially critical for the deleterious effects in adult and elderly cognitive performance.…”
supporting
confidence: 71%
“…7,8 Other studies demonstrate that chronic EtOH is more harmful, inducing greater long-term cognitive impairments when administered in adolescent animals than when this treatment is given in the adulthood. [9][10][11] Therefore, all this research confirms that both the way and the age of EtOH consumption is especially critical for the deleterious effects in adult and elderly cognitive performance.…”
supporting
confidence: 71%
“…Conversely, we observed that, independently of HFD consumption, mice exposed to EtOH presented deep disturbances on memory retrieval and learning, in line with previous reports showing that chronic and intermittent EtOH administration during adolescence decreases memory performance in the object recognition test [35,60,61]. Surprisingly, HFD (both ad libitum and binge) mitigated the effect of EtOH on the DI in the object recognition test, suggesting that HFD has a protective effect, which could be linked to an interference with EtOH pharmacokinetics, although this circumstance was not observed in a recent study carried out in our laboratory [16].…”
Section: Discussionsupporting
confidence: 92%
“…The present study evaluates, for the first time, the behavioral profile of adult animals that have been exposed during adolescence to EtOH binge drinking combined with an HFD. Taking into account previous studies modeling binge-drinking behavior [34,35], intermittent EtOH administration was administered to adolescent mice that had been exposed to either a standard diet (SD), continuous access to an HFD (ad libitum HFD), or limited and intermittent access to an HFD (Binge HFD). We sought to establish an eventual correlation between behavioral impairment and biochemical parameters associated with energy metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…Further research is needed to determine the long-lasting effects of cannabis and its derivatives on anxiety. With respect to the effects of cocaine abstinence, we demonstrated that cessation of cocaine administration in adult mice treated with saline during adolescence evoked anxiety-like behaviors, in agreement with earlier studies in rats [41,62,63,64,65,66] and mice [55]. However, a very interesting result of the present study is that the anxiety values displayed by the animals pre-treated with WIN and later with cocaine did not differ from those of control mice.…”
Section: Discussionsupporting
confidence: 90%
“…This incongruity could be explained by a ceiling effect on the disruption of PPI induced by WIN exposure. In an earlier study, we demonstrated that exposure to an EtOH binge-drinking procedure during adolescence, which is not able to alter the PPI by itself, impairs the startle reflex in mice exposed to the same cocaine withdrawal as that of the current study [55]. This supports the notion that previous drug exposure during the adolescent period may enhance the putative psychotic-like actions of cocaine in mice.…”
Section: Discussionsupporting
confidence: 88%